"No Girls on the Software Team": Internship Experiences of Women in Computer Science. (February 2023) - Lapan, Julia C.; Smith, Katie N.
Despite computer science (CS) students' widespread participation in internships, few studies have examined how internship experiences impact career decision-making. Because women are severely underrepresented within CS, understanding how internship experiences impact career decision-making can provide critical insight into women's career development processes and longevity in the field. Using the concept of career self-management within social cognitive career theory as a theoretical framework and standpoint feminism as a critical lens, we conducted interviews with 13 women CS majors to learn how internship experiences influenced their career decisions. Findings reveal three major career development process themes, including questioning technical competence, navigating gendered "microclimates, " and reflecting on careers in CS. While internships largely affirmed women's career interests in CS, participants also navigated challenging gendered dynamics and often made career decisions directly influenced by these experiences. Findings inform how CS educators, career development practitioners, and employers may better develop inclusive internship cultures in computing.